Intrinsic functional connectivity alterations of the primary visual cortex in patients with proliferative diabetic retinopathy: a seed-based resting-state fMRI study. (October 2020) - Yu, Yao; Lan, Dong-Yi; Tang, Li-Ying; Su, Ting; Li, Biao; Jiang, Nan; Liang, Rong-Bin; Ge, Qian-Min; Li, Qiu-Yu; Shao, Yi
Purpose: In this study, we aimed to investigate the differences in the intrinsic functional connectivity (iFC) of the primary visual cortex (V1), based on resting-state functional magnetic resonance imaging (rs-fMRI), between patients with proliferative diabetic retinopathy (PDR) and healthy controls (HCs). Methods: In total, 26 patients (12 males, 14 females) with PDR and 26 HCs (12 males, 14 females), matched for sex, age, and education status, were enrolled in the study. All individuals underwent rs-fMRI scans. We acquired iFC maps and compared the differences between PDR patients and the HCs. Results: The PDR group had significantly increased FC between the left V1 and the right middle frontal gyrus (RMFG), and significantly reduced FC between the left V1 and the cuneus/calcarine/precuneus. In addition, the PDR patients had significantly increased FC between the right V1 and the right superior frontal gyrus (RSFG), and significantly reduced FC between the right V1 and the cuneus/calcarine/precuneus. The individual areas under the curve (AUCs) of FC values for the left V1 were as follows: RMFG (0.871, p  < 0.001) and the cuneus/calcarine/precuneus (0.914, p  < 0.001), while the AUCs of FC values for the right V1 were as follows: RSFG (0.895, p  < 0.001) and the cuneus/calcarine/precuneus (0.918, p  < 0.001). Conclusions: The results demonstrated that, in PDR patients, altered iFC in distinct brain regions, including regions related to visual information processing and cognition. Considering the rise in the diabetes mellitus incidence rate and the consequences of PDR, the results could provide promising clues for exploring the neural mechanisms related to PDR and possible approaches for the early identification of PDR.